BIOPLASTIC PRESERVATION INNOVATION FROM INVERTEBRATE ANIMAL RESINS: A SUSTAINABLE SOLUTION TO INCREASE ECONOMIC VALUE IN KENJERAN COASTLINE - Sa’diyah, Halimatus; Rosalita, Anis; Firmansyah, Dani (Department of Biology Education, Faculty of Teacher Training and Education, Universitas Wijaya Kusuma Surabaya, 2024)
Kenjerann Beach is one of the beaches in Surabaya, which is located in the Bulakbull sub-district of Kenjeran which has a tourist attraction and is very beneficial for the community around the coast. The Kenjeran coast has potential biological resources such as marine biota and intervertebrate animals. This research aims to produce preserved invertebrates using bioplastic techniques and to increase knowledge and economic value of Kenjeran Beach. The research was carried out in two stages. The first stage is field observation to collect biota on the Kenjeran coast. The second step is the development of preservation technology, namely bioplastics. The model used in this research is at the implementation and testing stage. The results of these observations found 3 families of invertebrates that were used as materials and made it possible to preserve them. And these preserves can be used as accessories or decorations and other trinkets as business opportunities.